Genomic Comparison of Highly Virulent, Moderately Virulent, and Avirulent Strains From a Genetically Closely-Related MRSA ST239 Sub-lineage Provides Insights Into Pathogenesis - McClure, Jo-Ann M.; Lakhundi, Sahreena; Kashif, Ayesha; Conly, John M.; Zhang, Kunyan (Frontiers in Microbiology, 2018)
The genomic comparison of virulent (TW20), moderately virulent (CMRSA6/CMRSA3) and avirulent (M92) strains from a genetically closely-related MRSA ST239 sub-lineage revealed striking similarities in their genomes and antibiotic resistance profiles, despite differences in virulence and pathogenicity. The main differences were in the spa gene (coding for staphylococcal protein A), lpl genes (coding for lipoprotein-like membrane proteins), cta genes (genes involved in heme synthesis), and the dfrG gene (coding for a trimethoprim-resistant dihydrofolate reductase), as well as variations in the presence or content of some prophages and plasmids, which could explain the virulence differences of these strains. TW20 was positive for all genetic traits tested, compared to CMRSA6, CMRSA3 and M92. The major components differing among these strains included spa and lpl with TW20 carrying both whereas CMRSA6/CMRSA3 carry spa identical to TW20 but have a disrupted lpl. M92 is devoid of both these traits. Considering the role played by these components in innate immunity and virulence, it is predicted that since TW20 has both the components intact and functional, these traits contribute to its pathogenesis. However, CMRSA6/CMRSA3 are missing one of these components, hence their intermediately virulent nature. On the contrary, M92 is completely devoid of both the spa and lpl genes and is avirulent. Mobile genetic elements play a potential role in virulence. TW20 carries three prophages (ϕSa6, ϕSa3 and ϕSPβ-like), a pathogenicity island and 2 plasmids. CMRSA6, CMRSA3 and M92 contain variations in one or more of these components. The virulence associated genes in these components include staphylokinase, entertoxins, antibiotic/antiseptic/heavy metal resistance and bacterial persistence. Additionally, there are many hypothetical proteins (present with variations among strains) with unknown function in these mobile elements which could be making an important contribution in the virulence of these strains. The above mentioned repertoire of virulence components in TW20 likely contributes to its increased virulence, while the absence and/or modification of one or more of these components in CMRSA6/CMRSA3 and M92 likely affects the virulence of the strains.